Kedudukan Saksi Dalam Pembuatan Akta Notaris - Muhammad Resky Dirgananda; Suardi Suardi; Muh. Akbar Fhad Syahril; Aksah Kasim (Jurnal Litigasi Amsir, 2023)
This research was carried out aiming to find out the position and responsibilities of witnesses in making notarial deeds according to UUJN. As well as to find out the legal consequences that may arise if the witness does not maintain the confidentiality of the contents of the Notary Deed. The type of research used in this research is normative research. The results of the study show the position and responsibilities of witnesses in making notarial deeds according to UUJN. Namely the Legitimacy of an Authentic Deed through Formal Requirements, The position of a witness for a Notary deed is of course different from the position of a witness in general who is a witness who hears and/or sees an event that has occurred. civil liability, because this is in accordance with the elements in Article 1365 of the Indonesian Civil Code, with liability that obliges to compensate for losses suffered by one or several parties who feel aggrieved by the act. As well as the consequences for the witness if they do not maintain the confidentiality of the contents of the Notary Deed. According to the author, according to the author, the provisions regarding the obligation of witnesses to keep secret the contents of notarial deeds have added several paragraphs in Article 40 of Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning the Position of Notary Public. Article 170 paragraph (1) states that those who because of their work, dignity, or position are required to keep secrets, can ask to be released from the obligation to provide testimony as witnesses, namely regarding matters entrusted to them.